Religious Moderation in Indonesia According to Islamic Views - Kurniawati, Ani (Balai Diklat Keagamaan Ambon, 2023)
The emergence of various conflicts in multicultural countries, especially in Indonesia, is triggered by individual or group differences. Among these differences, religious differences are very sensitive to conflict. Although in fact few people use religion as a shield and eventually trigger conflicts between religions. From this fact, the government made a religious moderation policy as an effort to create harmony between religious communities. The purpose of this study is to find out the postulates of religious moderation in the Qur'an, Hadith and to find out the characteristics of religious moderation according to Islamic views. This is done to provide a basis for religious moderation policies implemented in Indonesia. By using literature review, which is looking for reading literature related to this research both from books, journals and news. As for analyzing data, researchers use content analysis as an effort to obtain valid data. This research resulted in findings that religious moderation has existed since the time of the Holy Prophetsa when the Qibla moved from Jerusalem to the Grand Mosque and also the hadith narrated by Bukhari Muslim describes the attitude of wasathan. Religious moderation is an effort to be middle between two attitudes with the characteristics of the spread of Islam without violence, modern way of life, rational thinking, using a contextual approach and also being able to use the ijtihad method in determining the law of a case.